Planning, Implementing, and Evaluating a Program to Address the Oral Health Needs of Aboriginal Children in Port Augusta, Australia - E. J. Parker; G. Misan; M. Shearer; L. Richards; A. Russell; H. Mills; L. M. Jamieson (International Journal of Pediatrics)
Aboriginal Australian children experience profound oral health disparities relative to their non-Aboriginal counterparts. In response to community concerns regarding Aboriginal child oral health in the regional town of Port Augusta, South Australia, a child dental health service was established within a Community Controlled Aboriginal Health Service. A partnership approach was employed with the key aims of (1) quantifying rates of dental service utilisation, (2) identifying factors influencing participation, and (3) planning and establishing a program for delivery of Aboriginal children’s dental services that would increase participation and adapt to community needs. In planning the program, levels of participation were quantified and key issues identified through semistructured interviews. After 3.5 years, the participation rate for dental care among the target population increased from 53 to 70 percent. Key areas were identified to encourage further improvements and ensure sustainability in Aboriginal child oral health in this regional location.